Beyond Availability: Towards a Deeper Understanding of Machine Failure Characteristics in Large Distributed Systems - Yalagandula, Praveen; Nath, Suman; Yu, Haifeng; Gibbons, Phillip B.; Seshan, Srinivasan (WORLDS'04: First Workshop on Real, Large Distributed Systems, 2004)
Although many previous research efforts have investigated machine failure characteristics in distributed systems, availability research has reached a point where properties beyond these initial ﬁndings become important. In this paper, we analyze traces from three large distributed systems to answer several subtle questions regarding machine failure characteristics. Based on our ﬁndings, we derive a set of fundamental principles for designing highly available distributed systems. Using several case studies, we further show that our design principles can signiﬁcantly inﬂuence the availability design choices in existing systems.